TEACHING ENGLISH GRAMMAR BY VERBAL INSTRUCTION RULES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In understanding English texts according to their specialty by reading, grammar plays great role and it is very important teaching them. That is why the article is dedicated one of the methods of teaching receptive grammar of English language, the passive voice sentences in the process of reading the mathematical texts. Taking into consideration the scientific works of famous physiologic and methodological scientists are worked out quantum “rule-instructions” for teaching recognizing and understanding the sentences with passive constructions to students of math faculty. "The first rule-instruction" are divided into twelve quanta (a, b, c, d, e, f, g, h, i, g, k, l). It has worked out the complex of exercises for mastering the given information about the passive construction after each "rule instruction". The exercises are created according to the principle “from easy to complex”. The sentences with passive construction are presented in the micro texts. The passive construction is separated with red color (or it is underlined).